Penerapan Model Pembelajaran Problem Solving Fisika pada Konsep Listrik Dinamis di SMA IT IQRA Kota Bengkulu - Fitri Nur Khairi; Muhammad Farid; Eko Swistoro (PendIPA Journal of Science Education, 2019)
Abstract[Application of Physics Problem Solving Learning Model on the Concept of Dynamic Electricity in SMA IT IQRA Bengkulu City]. This study aims to explain improvement of cognitive learning outcomes of students and differences in student learning outcomes of low, medium, and high group on the concept of dynamic electricity by applying the model of Problem Solving Physics Problem. This research is a Pre-experiment research of One Group Pretest-Posttest design. The study was conducted at IQRA IT Bengkulu  in Extracurricular Learning 20 students. Learning media used in learning is stem kedondong (Spondias dulcis). The Increasing cognitive learning outcomes were analyzed descriptively and calculated by normalized gain scores and analyzed by Anova test. The results show that high group N-gain of 0.71, medium group 0,56, and low group by 0,49. The result of the anava test show the value of Fh 27,89> Ft 3,59 with significant 5% and 6,11 at significant level 1%. The conclusion of this research 1) the application of the learning model of Problem Solving Physics on the concept of dynamic Electricity can improve students' cognitive learning outcomes 2) there are differences in learning outcomes for high, medium and lower class students. Keywords: Learning model; Problem Solving Physics; Dynamic Electricity; Learning Outcomes. (Received December 6, 2018; Accepted March 29, 2019; Published June 19, 2019) AbstrakPenelitian ini bertujuan untuk menjelaskan peningkatan hasil belajar kognitif siswa dan perbedaan hasil belajar siswa kelompok rendah, sedang, dan tinggi  pada konsep listrik dinamis dengan menerapkan model pembelajaran Problem Solving Fisika.Jenis penelitian ini adalah Pre-ekperimen desain One Group Pretest-Posttest. Penelitian dilakukan di SMA IT IQRA kota Bengkulu pada pembelajaran Ekstrakurikuler. Media pembelajaran yang digunakan dalam pembelajaran adalah batang pohon kedondong (Spondias dulcis).Peningkatan hasil belajar kognitif dianalisis secara deskriptif dan dihitung dengan skor gain yang dinormalisasi serta dianalisis dengan uji Anova. Hasil penelitian menunjukkan N-gain kelompok tinggi sebesar 0,71, kelompok sedang 0,56, dan kelompok rendah sebesar 0,49. Hasil uji anava menunjukkan nilai Fhitung 27,89 > Ftabel 3,59 dengan signifikan 5% dan 6,11 pada taraf signifikan 1%. Kesimpulan dari penelitian ini 1) penerapan model pembelajaran Problem Solving Fisika  pada konsep Listrik dinamis dapat meningkatkan hasil belajar kognitif siswa 2) terdapat perbedaan hasil belajar siswa kelompok atas, sedang dan bawah. Kata kunci: Model pembelajaran Problem Solving Fisika, Listrik Dinamis, Hasil belajar